Design of a Participatory Web-Based Geographic Information System for Determining Industrial Zones. (5th March 2021) - Chumaidiyah, Endang; Dewantoro, Mouli De Rizka; Kamil, Anton Abdulbasah
Abstract : Different types of site selection exploited by geographic information systems (GIS) by combining various types of data relate to the purpose of site selection. In reality, numerous factors including physical, environmental, and social factors affect the site selection in terms of deciding the location of a new industry. Accordingly, this paper conceives systems for determining new industrial zones in the form of web-based applications or ordinarily called web-based GIS. Thus, the application named the potential industrial zone smart systems, in which the prototype of the application is able to facilitate planning the determination of new industrial zone based on six parameters throughout the analytical hierarchy process method. The result weights of six criteria are soil type 35%, land use 32%, land slope 15%, the distance of land to river 9%, the distance of land from road and accessibility 5%, and the distance of land to public facilities 4%. Additionally, the web-based GIS is a user-friendly application to determine the planned industrial location. Further, the demonstration runs effortlessly in exhibiting data on the potential of new industrial zones in the city of Bekasi, West Java Province of Indonesia.